Reactions of green lizards (Lacerta viridis) to major repellent compounds secreted by Graphosoma lineatum (Heteroptera: Pentatomidae) - Gregorovičová, Martina; Černíková, Alena (Zoology (Jena, Germany), 2015)
The chemical defence of Heteroptera is primarily based on repellent secretions which signal the potential toxicity of the bug to its predators. We tested the aversive reactions of green lizards (Lacerta viridis) towards the major compounds of the defensive secretion of Graphosoma lineatum, specifically: (i) a mixture of three aldehydes: (E)-hex-2-enal, (E)-oct-2-enal, (E)-dec-2-enal; (ii) a mixture of these three aldehydes and tridecane; (iii) oxoaldehyde: (E)-4-oxohex-2-enal; (iv) secretion extracted from metathoracic scent glands of G. lineatum adults and (v) hexane as a non-polar solvent. All chemicals were presented on a palatable food (Tenebrio molitor larvae). The aversive reactions of the green lizards towards the mealworms were evaluated by observing the approach latencies, attack latencies and approach-attack intervals. The green lizards exhibited a strong aversive reaction to the mixture of three aldehydes. Tridecane reduced the aversive reaction to the aldehyde mixture. Oxoaldehyde caused the weakest, but still significant, aversive reaction. The secretion from whole metathoracic scent glands also clearly had an aversive effect on the green lizards. Moreover, when a living specimen of G. lineatum or Pyrrhocoris apterus (another aposematic red-and-black prey) was presented to the green lizards before the trials with the aldehyde mixture, the aversive effect of the mixture was enhanced. In conclusion, the mixture of three aldehydes had the strong aversive effect and could signal the potential toxicity of G. lineatum to the green lizards.
Keywords: Animals; Aldehydes; Repellent secretion; stravovací zvyklosti; Aversive reaction; Chemical defence; ještěři; aldehydy; zvířata; pachové žlázy; Scent Glands; Graphosoma lineatum; Feeding Behavior; Aposematism; Lizards; Heteroptera